AN ANALYSIS AND IMPLEMENTATION OF OBJECT RECOGNITION ALGORITHMS FOR SURVEILLANCE SYSTEMS - Hamiyev A.T; Kholiyorov Kh.A; Toshboey J.S (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract This paper delves into the development of algorithms for recognizing abandoned objects in video surveillance systems. With the increasing importance of security in public spaces, such as airports and stadiums, the need for efficient and accurate video analysis tools has become paramount. This study explores various methodologies, including statistical methods, background modeling, and boosting techniques, to improve object detection accuracy. Additionally, the implementation of these algorithms using Python and machine learning frameworks such as OpenCV, TensorFlow, and PyTorch is discussed.